A STUDY ON MODAL ADJUNCTS IN THE MENTAL PROCESS IN ENGLISH AND VIETNAMESE NEWSPAPERS - Assoc. Prof. Dr. PHAN VĂN HÒA (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Identifying or using Modal Adjuncts, especially in the Mental Process has always been a challenge to Vietnamese learners of English. So, this study aimed to discover the syntactic, semantic and pragmatic features of Modal Adjuncts in English and Vietnamese. With the items of sports newspapers in English and Vietnamese collected, we have explored some linguistic features of Modal Adjuncts in the Men and the similarities and differences of Modal Adjuncts between English and Vietnamese in terms of syntactic, semantics and pragmatics. Besides, quantitative analyses have also been carried out to show how English and Vietnamese people use Modal Adjuncts in English and Vietnamese sports newspapers. In addition, this research helps learners of the two languages achieve better communicative competence and use Modal Adjuncts effectively in their concrete communication situations.